Tragedy and Triumph Early Testimonies of Jewish Survivors of World War II - Hodge, Freda (History, 2018)
In this collection Freda Hodge retrieves early voices of Holocaust survivors. Men, women and children relate experiences of deportation and ghettoisation, forced labour camps and death camps, death marches and liberation. As Feliks Tych points out, such eye-witness accounts collected in the immediate post-war period constitute the most important body of Jewish documents pertaining to the history of the Holocaust. The freshness of memory makes these early voices profoundly different from, and historically more significant than, later recollections gathered in oral history programs. Carefully selected and painstakingly translated, these survivor accounts were first published between 1946 and 1948 in the Yiddish journal Fun Letzten Khurben ('From the Last Destruction') in postwar Germany, by refugees waiting in 'Displaced Person' camps, in the American zone of occupation, for the arrival of travel documents and visas. These accounts have not previously been available in English.